Peningkatan Literasi Perpajakan UKM melalui Optimalisasi Insentif 0,5% dan Kemudahan Pelaporan SPT Badan - Featy Octaviany; Yuszak M. Yahya; Srihadi Winarningsih; Wahyudin Zarkasyi; Citra Sukmadilaga (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aimed to enhance tax literacy and the readiness of Small and Medium Enterprise (SME) owners for the implementation of the Coretax System while optimizing the 0.5% tax incentive. The method employed was an interactive online webinar featuring expert speakers from academia, tax consultants, and the Directorate General of Taxes. The results demonstrate a significant improvement in participants' comprehension regarding the transition to the integrated Coretax System. SME owners were able to identify the correct procedures for utilizing the 0.5% final tax incentive to enhance business financial efficiency. Furthermore, the findings indicate that direct engagement with tax authorities reduced apprehension concerning the complexity of Corporate Tax Returns (SPT Badan) by highlighting the automation features within the new system. In conclusion, the webinar served as a vital communication channel between regulatory bodies and the practical requirements of business owners. Ongoing educational initiatives are necessary to ensure that the adoption of tax technology fosters voluntary compliance and supports national economic growth.